The Clinical Features of Vernal Conjunctivitis in Cicendo National Eye Hospital - Naylovar Farsya; Sesy Caesarya; Irawati Irfani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction: Vernal conjunctivitis is a chronic, recurrent form of allergic conjunctivitis that occurs mainly in children and is commonly found in warm and humid climates or tropical countries, including Indonesia. Although vernal conjunctivitis is a self-limiting disease, it often leads to visual impairment and significantly affects the patient's quality of life. Methods: This retrospective descriptive study was conducted in Cicendo National Eye Hospital from March to April 2023 using the total sampling method to obtain the clinical features of vernal conjunctivitis patients. Result: This study took 117 patients (234 eyes) registered in electronic medical records from January to December 2022 with an age range of 7-18 years. The mean age of the patients was 10.73 ± 3.02 years, with total of 78 patients (66.67%) being male. A total of 30 patients (25.64%) had a history of atopic allergies. All patients in this study had a bilateral condition. The palpebral type was diagnosed in 85 patients (72.64%). Red eyes were the most prominent symptom experienced in 89 eyes (76.06%). Papillary signs were seen in 203 eyes (86.75%), with an uncorrected visual acuity of 6/6 to 6/18 were found in 163 eyes (69.66%). A small proportion of patients experienced complications in 93 eyes (39.74%). Conclusion: The clinical features of vernal conjunctivitis patients in Cicendo National Eye Hospital are similar to those in other tropical countries. Most patients were male and complained of itching and red eyes. The palpebral type is the most common type. Few distinct features were noted indicating a low association with atopy.